A Method for Determining the Axial Displacement of Rotating Parts Using a Line Scan Camera - FORGÁCS Zsófia (Journal of Electrical and Electronics Engineering)
This paper presents a novel method for evaluating the axial displacement of rotating components using line scan cameras. Developed in collaboration with an automotive manufacturer, this approach enables non-contact, non-invasive inspection of starter motors, allowing for the measurement of rotational speed and gear backlash without disassembly. The method leverages line scan cameras and statistical image processing techniques to analyze recorded images, examining the variance profiles of pixel arrays to determine component displacement. The solution ensures precise measurement while minimizing the need for costly equipment, addressing the growing significance of machine vision technology across various industrial sectors.